ENVIRONMENTALLY CONSCIOUS ISLAMIC EDUCATION CURRICULUM DESIGN (ECO-THEOLOGY) - Soimatul Khomisah; Husna Nashihin; Eri Twi Cahyanti; Khailani Khumairoh (Proceeding of International Conference of Islamic Education, 2025)
The curriculum of Islamic education with environmental insight through the eco-theology approach is a response to the global ecological crisis and ecological moral degradation. The main objective of this study is to formulate an integrative curriculum design between Islamic values ​​and environmental awareness in the context of formal education. The method used is qualitative descriptive with data collection techniques through literature studies, documentation, and in-depth interviews with Islamic and environmental education experts. Data analysis was carried out thematically to identify relevant Islamic principles in forming ecological awareness. The results of the study show that the integration of the values ​​of tauhid, amanah, and khalifah in the curriculum structure is able to form the character of students who care and are responsible for nature. This curriculum includes strengthening spiritual, cognitive, and social action competencies in contextual and transdisciplinary learning. The conclusion of this study emphasizes the importance of updating the Islamic education curriculum that is responsive to environmental issues, not only as an additional aspect, but as the main framework for character formation and sustainability of life. The curriculum with eco-theology insight plays a strategic role in creating a generation of Muslims who are environmentally aware and globally competitive.